PELATIHAN PEMROGRAMAN WEB PERSONAL BRANDING MENGGUNAKAN FRAMEWORK LARAVEL DI SMK TELKOM LAMPUNG - Debby Alita; Selamet Samsugi; Permata Permata; Riska Amalia Praptiwi; Lathifah L (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
The need to access the latest information in the form of images, text, videos, animations, and more from various sources through websites using smartphones, tablets, laptops, and PCs connected to the internet is being done by everyone in today's era. Therefore, the need for human resources to create or develop web-based technology in institutions is highly required. Web-based technology is created to help solve problems in these institutions. In addition to supporting web-based technology, the acceleration of mastering software development technology is also carried out, including the development of frameworks. One of the latest and widely used web-based system frameworks today is Laravel. Knowledge of web programming needs to be conveyed early on, such as in vocational high schools for majors that lead to producing software engineering professionals. SMK Telkom Lampung is one of the vocational high schools that has an RPL major. Therefore, it is necessary to carry out Community Service by conducting web programming training using the Laravel framework for students in the Software Engineering major at SMK Telkom Lampung, who are still learning using native web pages. The training was held for 1 day on Friday, February 24th, 2023, in the Computer Laboratory of SMK Telkom Lampung and was attended by 19 RPL major students. Some of the software that supported the training were xampp, composer, and Laravel 8.*. The evaluation results of the training showed that 100% of the participants were able to understand, interested, and motivated by the material presented.